Risque naturel, tensions sociales et défiance politique : la tempête Fiona, un récit et quelques leçons d’une crise - Jean-Pierre Bellanger (EchoGéo, 2023)
Territorial knowledge is also measured by unexpected events such as natural hazards. In such circumstances, the population loses its usual points of reference, leading it to question its practices and make new choices guided by experience. This article is primarily exploratory in nature, and sets out to identify and describe some of the lessons learned from the conflicting, ambiguous and ambivalent relationships between the public and their elected representatives in times of climate crisis. Our field of study is Guadeloupe, following the passage of tropical storm Fiona on 16 and 17 September 2022, a period during which very significant material damage was recorded and one direct death deplored.